Pengaruh Promosi dan Lokasi terhadap Keputusan Pembelian Rumah Subsidi di Kecamatan Buleleng - Pande Putu Dylan Maharani; I Nyoman Sujana (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine: (1) the effect of promotion on the decision to purchase subsidized houses, (2) the effect of location on the decision to purchase subsidized houses, and (3) the effect of promotion and location on the decision to purchase subsidized houses. This study is a causal quantitative study. The population of the study was all consumers of subsidized houses in Buleleng District. The number of samples of 183 respondents was determined using purposive sampling techniques. Data collection used questionnaires and interviews. Data analysis used multiple linear regression with the help of SPSS version 25. The results of the study showed that (1) promotion had a positive and significant effect on purchasing decisions, (2) location had a positive and significant effect on purchasing decisions, and (3) promotion and location had a positive and significant effect on purchasing decisions of subsidized houses in Buleleng District.